(untitled) (Maslahah: Journal of Islamic Studies, 2022)
Divorce often makes hadhanah in dispute by husbands and wives who are divorced. Therefore, the rights of a child are not fulfilled or neglected and there is also confusion over control for many reasons. Hadhanah is something that must be done for the good of the child itself, so that if the parents divorce the child will still have the love of both parents. As in Article 2 of Law Number 4 of 1979 which discusses children’s rights to obtain welfare. With regard to child care, for children who are under 12 years of age, the care falls on the mother. As long as the mother does not have a cause/reason that can prevent or abort the mother from carrying out hadhanah. The first thing that must be considered in caring for the child is the ability, the ability to provide a sense of security and peace for the child who is a divorce victim.